Innovation Strategy and Customer Loyalty for Indonesian Freight Forwarding Company - Fauzia, Elfa; Pahala, Yosi; Thamrin, Muhammad; Abidin, Zaenal; Perwitasari, Erni Pratiwi (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
One of the problems in logistics companies in Indonesia is the fact that some companies have not implemented Innovation strategies properly in the Pre-Booking and Forecast Expectancy Container systems in shipping companies so that it is quite difficult for customers to get Delivery Orders for the export shipping process. The company creates ways to maintain customer loyalty by implementing innovation strategies and service quality in the company's operational performance. The aim of this research is to determine and analyze the influence of innovation strategies and service quality on operational performance on customer loyalty. This qualitative research uses path analysis. The sample taken was 30 respondents with the criteria of Freight Forwarding company customers who had worked at their company for at least one year in the position of Logistics staff. Based on the data analysis carried out, it was concluded that the innovation strategy variable had no individual or partial influence on employee performance. The service quality variable does not have an individual or partial influence on employee performance. Employee performance variables do not have an individual or partial influence on customer loyalty. However, innovation strategy, service quality and operational performance together or simultaneously have a positive effect on customer loyalty.